Implementation of National Drug Policy in Different Countries: An Appraisal and Experience from Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Key Words: National Drug Policy; World Health Organization; Bangladesh.DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9442 JBCPS 2011; 29(3): 177-179